2018
DOI: 10.1080/01676830.2018.1435694
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab as first treatment option in optic neuropathy secondary to Graves’ orbitopathy

Abstract: Dysthyroid optic neuropathy (DON) is one of the complications that can affect Graves' orbitopathy (GO) patients. Its prevalence is estimated at less than 5%. It is usually treated with intravenous steroids, radiotherapy or orbital decompression. Tocilizumab has been proposed as a treatment option in cases of GO refractory to steroid treatment, with good clinical results. Our aim is to report the case of a patient with optic neuropathy secondary to GO treated with tocilizumab as primary treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Tocilizumab was first introduced as a treatment for severe glucocorticoid-resistant GO in 2009, with the first results published in a small case series [18]. The efficacy of tocilizumab was later supported by a randomized clinical trial in patients with active steroid-resistant GO [19], as well as by several case reports and case series [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Tocilizumab was first introduced as a treatment for severe glucocorticoid-resistant GO in 2009, with the first results published in a small case series [18]. The efficacy of tocilizumab was later supported by a randomized clinical trial in patients with active steroid-resistant GO [19], as well as by several case reports and case series [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…A TNF α-blocker, infliximab, has been employed in one such case and noted positive results [138]. TCZ was used in 2 DON cases: one DON case was included in the initial cohort reported by Moreiras-Perez et al [122] and another one was reported by Pascual-Camps et al [139] very recently. In both cases, TCZ therapy was deemed successful.…”
Section: Therapy For Dysthyroid Optic Neuropathymentioning
confidence: 99%
“…Orbital radiotherapy is indicated as adjuvant treatment. Some case reports describe the use of new immunological treatment (as tocilizumab) 14 but given the lack of larger scale studies, we cannot consider these treatments as conventional DON therapy. So far, just one randomized study compares medical versus surgical treatment for DON 3 leading to EUGOGO recommendations for intra-venous corticoids as first-line treatment before surgery.…”
Section: Don Represents Both Diagnostic and Therapeutic Challengesmentioning
confidence: 99%
“…The follow-up data were collected between 2 and 46 months after the last treatment for each patient (median follow-up at 8 months;[4][5][6][7][8][9][10][11][12][13][14]. The follow-up data were collected between 2 and 46 months after the last treatment for each patient (median follow-up at 8 months;[4][5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%